2004
DOI: 10.1111/j.1365-2621.2004.tb10990.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Treatment Temperature on Fresh‐cut Cantaloupe Melon during Storage

Abstract: The effect of calcium treatment temperature on cut cantaloupe fruit during storage was determined. Fruit dipped in calcium solution at 4 °C had lower respiration and moisture loss rates than treated fruit at ambient temperature. Calcium treatment lowered lipase activity at both temperatures, but the effect was more notable in fruit treated at the lower temperature where lipase activity was undetectable in the freshly processed fruit and after storage for 24 h. The ability of calcium to confer rigidity to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
1
25
0
3
Order By: Relevance
“…The samples treated with the hot water and NaCl combination solution showed the lowest respiration rates (5.09 mL CO2/kg・hr) at day 8 days of storage period, while hot water-treated samples reached values of 6.97 mL C0 2 /kg・hr. Similarly, Lamikanra and Watson (2004) and Luna-Guzmán and Barrett (2000) found a reduction in respiratory rates in fresh-cut cantaloupe melon treated with CaCl 2 and lactate, in terms of ripening, which delayed the senescence as a result of the combined additive effects of hot water dipping and calcium salts. Hence, the combination of heat and anti-browning agents were very effective in markedly reducing the respiration rate of burdocks.…”
Section: Respiration Ratementioning
confidence: 99%
“…The samples treated with the hot water and NaCl combination solution showed the lowest respiration rates (5.09 mL CO2/kg・hr) at day 8 days of storage period, while hot water-treated samples reached values of 6.97 mL C0 2 /kg・hr. Similarly, Lamikanra and Watson (2004) and Luna-Guzmán and Barrett (2000) found a reduction in respiratory rates in fresh-cut cantaloupe melon treated with CaCl 2 and lactate, in terms of ripening, which delayed the senescence as a result of the combined additive effects of hot water dipping and calcium salts. Hence, the combination of heat and anti-browning agents were very effective in markedly reducing the respiration rate of burdocks.…”
Section: Respiration Ratementioning
confidence: 99%
“…Both of these variables showed a positive effect on shear force indicating increase in shear force with increase in the levels of these variables (Table 4). Lamikanra and Watson (2004) also found calcium chloride dip pretreatment as an effective means in maintaining the hardness of fresh cut cantaloupe melons during storage. Sugar blanching has also been reported helpful in maintaining the textural characteristics of tissue during dehydration of fruits and vegetables (Jayaraman & Dasgupta, 1992).…”
Section: Effect Of Variables On Shear Forcementioning
confidence: 94%
“…All the three variables affected the drip at linear, quadratic and interactive levels. Calcium chloride soaking pretreatment is known for maintaining the texture of cut fruits and vegetables as it forms insoluble calcium pectate by reacting with the soluble pectic acid present in the middle lamella of the cells (Lamikanra & Watson, 2004). In the case Table 3 Analysis of variance data for response variables.…”
Section: Effect Of Variables On Syneresis (Drip Loss)mentioning
confidence: 99%
“…Previous research has shown that calcium plays a significant role in reducing mechanical damage of both climacteric and non-climacteric fruits (Lamikanra and Watson, 2004). If the activities of PG and PME can be reduced in the whole fruit via application of calcium in dragon fruit as observed in the fresh-cut dragon fruit (Chuni et al, 2010), the longevity of the fruit can be extended.…”
Section: Ajabsmentioning
confidence: 99%